A novel recovery process for lipids from microalgæ for biodiesel production using a hydrated phosphonium ionic liquid. Issue 5 (12th May 2015) - Olkiewicz, Magdalena; Caporgno, Martin P.; Font, Josep; Legrand, Jack; Lepine, Olivier; Plechkova, Natalia V.; Pruvost, Jeremy; Seddon, Kenneth R.; Bengoa, Christophe
<x xml:space="preserve">Abstract</x> A novel process for recovering lipids from microalgæ using a hydrated ionic liquid is presented.